Work-life balance and well-being of graduate students. (1st October 2020) - Yusuf, Juita-Elena (Wie); Saitgalina, Marina; Chapman, David W.
ABSTRACT: This exploratory study examines issues related to work-life balance and well-being of a diverse population of graduate students, including master's and doctoral students, full-time and part-time graduate students, on-campus and on-line students, and from multiple disciplines. Using data from graduate students at a large, public university on the mid-Atlantic coast, our results provide a broad picture of work-life balance, three components of well-being – quality of life, physical health, and mental health – and factors such as program climate, sense of well-being, stressors, and sources of support. We discuss how social cognitive, structuration, and border theories can be applied to study and address issues of work-life balance and well-being in more depth.